AN ANALYSIS OF AGE AND OWNERSHIP STRUCTURES OF SMALL SCALE INDUSTRIAL ESTABLISHEMENTS IN ONDO STATE - Francis, Fatusin Afolabi (European Scientific Journal, ESJ, 2012)
The study focused on an examination of age and ownership structures of small scale industrial establishments in Ondo State of Nigeria. This was with a view to assessing the survival rates as will as the structure of enterprises’ owners. The study made use of 353 questionnaires which constituted 25% of enterprises administered on nine settlements proportionately on basis of existing enterprises in each settlement. These were analysed using descriptive methods. The study found out that over 48% of existing enterprises with some variation across the 3 sampled regions were established between year 2000 and 2012. Moreover, only 1.7% of existing enterprises were those established before year 1970. This reflects high mortality rates among the enterprises. Moreover the structure of ownership revealed dominance of sole proprietorship accounting for over 90% of all enterprises owners. This has its problems since sole proprietors are considerably constrained in term of finance and managerial capability, they often find it hard to survive. As a way forward the study recommends more governmental support in terms of improved access to finance and training.